Impacto socioeconómico de la organización de un evento deportivo de talla mundial: análisis comparativo de las copas del mundo Sudáfrica 2010 - Brasil 2014. (2022)
During this investigation, a retrospective of two host countries for a soccer World Cup (Brazil and South Africa) was carried out, speaking directly in the economic and social part, in order to be able to demonstrate economic growth and social development or the lack of these after the holding a World Cup. In this thesis the economic and social situation of Brazil will be studied, and the improvements that the different works and projects that were carried out can suppose. In addition, the World Cups held in 2010 and 2014 were compared, where socioeconomic aspects of these countries were also studied.